Utilisation of performance analysis amongst Western Province club rugby coaches - Painczyk, H. F. (Stellenbosch University, 2018)
The use of performance analysis (PA) by coaches has significantly increased across many sporting codes around the world. The demand for effective feedback due to memory retention limitations in the coaching process is a main contributing factor. Researchers have investigated the utilisation of performance analysis within certain coaching populations and found that it is used extensively in the coaching and feedback process. Its popularity and importance in drawing accurate conclusions regarding athletic performance has led to the investigation of the inter- and intra-coder reliability of the computerised notational systems used to produce this data. However, there are many systems that are available to coaches that have not yet been tested. The first objective of this study was to determine and compare the utilisation of performance analysis by Western Province Rugby Union club rugby coaches. This was carried out with the aim of providing insight into the extent to which PA is currently being used in a practical setting. The second objective of this study was twofold: firstly, to determine the inter- and intra-coder reliability of the EncodeProRX performance analysis software and secondly to compare coding done by novice coders and an experienced coder. This thesis is structured as a series of research articles. Article 1: `Utilisation of Performance Analysis among Western Province Rugby Union Club Coaches` addresses the first objective: it highlighted that only 16% of coaches in the Super League have access to video footage after every game, with 39% of coaches never having access to video footage. It also highlighted that 80% of coaches value performance analysis strongly, yet 82% do not have access to a computerised notational system. The number of coaches that do not have access to video and computerised notational systems can be attributed to the fact that 80% of coaches do not receive a budget for performance analysis resources from their clubs. Despite this, 76% of coaches perform their own analysis, to some extent, indicating that they are aware of their memory retention issues but lack the resources to do this effectively. Article 2: `Reliability of EncodeProRX performance analysis software to assess rugby performance` addresses the second objective. The EncodeProRX system showed very good inter-coder reliability agreement among most of the performance indicators measured, namely scrums (K=.93), lineouts (K=.93), handling errors (K=.90), tackles Stellenbosch University https://scholar.sun.ac.za v (K=.83), mauls (K=.92) and rucks (K=.92). There was an average agreement of K=.79 across all the performance indicators. Furthermore, the intra-coder reliability showed an average agreement of K=.82 which shows that coders can use this system consistently. When comparing an experienced coder to the novice coders, there was some variability with two coders yielding very good agreement (K=.81 and K=.84) and three coders with good agreement (K=.69, K=.72 and K=.79). This study concluded that there is an unfavourable situation in Western Province club rugby where many coaches do not have access to performance analysis resources. The primary contributing factor of this was budget related issues. The EncodeProRX performance analysis system was proven to have good inter- and intra-coder reliability meaning that it is an affordable computerised notational system available to coaches that can be used to determine effective training protocols and provide precise operational definitions.